Empowering Learner Soft Skills in Digital Teaching: A Study of Teacher Perspectives - Yentri Anggeraini; Fitria Aprilia; Muhammad Yazir; Lianasari; Nopa Yusnilita (Journal of English Language Learning, 2025)
The necessity of soft skills for digital native learners is paramount, underscoring the urgency of integrating them into pedagogical processes to equip students with essential life competencies for navigating the digital age. This study investigates English educators' perspectives and implementation strategies for fostering eight key soft skills (communication, collaboration, critical thinking, creativity, adaptability, emotional intelligence, leadership, and time management) within the English as a Foreign Language (EFL) classroom. A mixed-methods approach was employed, gathering data from 35 English teachers using both interviews and a closed-ended questionnaire. The qualitative and quantitative analysis revealed that teachers successfully implement a range of project-based and interactive activities. Specifically, the findings demonstrate that activities such as peer tutoring, role-playing, mini drama projects, group presentations, reader's theatre, and self-peer feedback are effective in empowering all eight targeted soft skills in EFL learners. The study concludes that diversified and project-based activities are highly effective pedagogical tools for the simultaneous development of a broad spectrum of soft skills in the digital teaching environment. These findings offer practical implications for curriculum designers and educators seeking to enhance soft skill development in language education.